Empirical investigation of indoor environmental quality (IEQ) in a hospital building in Merida Yucatan, Mexico - C. Cocom Martínez, Fanny; ., . (International Journal of Engineering and Technology, 2018)
This research summarizes the result of physical measurement of the indoor environmental quality (IEQ) in two different hospital rooms, from a small hospital in Merida Yucatan, Mexico. The results show wide differences in the established parameters for this evaluation and the measures obtained. The temperature levels exceed the range of 20-26ºC in both rooms, considering that bothrooms have air conditioning system (ISO 7730, 2005). The levels of Relative Humidity also exceed in more than 20% of the permitted range. The amount of CO2 is registered in higher levels when the air conditioning system is on, this is due to the lack of circulation and proper ventilation (ASHRAE 62.1, 2016). About Light Intensity showing the difference between rooms, is represented in the obtained results in the established parameters and their physical characteristics (NOM-025-STPS, 2008). Optimum conditions in indoor environments should result in health, well-being and comfort, both in terms of working life and in the areas where healthcare is concerned. The current society demands safe, clean and well-conditioned places, for which it is necessary to integrate perceptions and demands of the users to reach an optimal balance between social and legislative standards.